Laboratory Diagnosis of APC-Resistance: A Critical Evaluation of the Test and the Development of Diagnostic Criteria - de Ronde, Hans; Bertina, Rogier M (Thrombosis and Haemostasis, 1994)
The APC-resistance test consists of two APTT’s, one in the presence and one in the absence of a fixed amount of Activated Protein C (APC), and is a simple and reliable method to detect a reduced sensitivity to the anticoagulant action of APC (APC-resistance). At a fixed concentration of APC the prolongation of the APTT is dependent on the activator, the CaCl2 concentration, the citrate concentration in the sample, and on sample handling. The effect of sample handling can be reduced by calculating the APC-Sensitivity Ratio (APC-SR). The actual prolongation of the APTT is also influenced by low protein S levels (reduction of APC-SR) and by reduced levels of factors V, VIII and IX (increase of APC-SR). The APC-SR is most dramaticly effected by reduced levels of factors II and X, which result often in “unmeasurable” APC-SR’s in plasmas of patients on oral anticoagulant treatment. So at present no reliable APC-SR’s can be measured in these patients. Patients treated with heparin can be tested after treatment of their plasma with Hepzym®. The inter- and intra-assay variation in the APC-SR is 4% and 2%, respectively, when using the same batches of activator and APC. The variation which is introduced in the APC-SR by use of different batches of activator or APC, or by the use of different APC or CaCl2 concentrations, can effectively be avoided by expressing the result of the test in normalized-APC-SR (n-APC-SR).The diagnosis of APC-resistance is defined by a n-APC-SR < 0.84. Patients who are heterozygous for the Factor V Leiden mutation have a n-APC-SR of 0.45-0.70, while patients who are homozygous for the mutation have a n-APC-SR <0.45.